(untitled) (Itinera, 2017)
The paper aims to investigate the idea of taste in the comedies of Carlo Goldoni. In 1750 Goldoni presents on the stageÂ Il cavaliere di buon gusto, where good taste is characterized by measure and dignity in manners and conduct in everyday life this optimistic idea is changing and in 1762 with Una delle ultime sere di Carnevale, the way of life of the characters and their relationship to the society are problematic e melancholic. The good taste is now a new mixing of comic and pathetic, that Goldoni seeks to introduce in hisÂ theatrical works for the Comedie Italienne, during his stay in Paris. Â Â